Peningkatan Pemahaman Anak Didik Pemasyarakatan di LPKA kelas II Pekanbaru tentang Standar Layanan Bantuan Hukum - Zulkarnain Noerdin; Robert Libra Robert (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The need for understanding on improving correctional students at LPKA class II Pekanbaru regarding the RI Minister of Law and Human Rights Number 4 of 2021 concerning Legal Aid Service Standards is Very Urgent. This activity was carried out on April 26, 2021, at LPKA Pekanbaru in the form of lectures, dialogues, and discussions to solve the problems faced. The working procedures to support the methods offered are lectures held, dialogue, and discussion. Partner participation in this community service event provides a place and time for program implementation and presents partner members as audiences. According to this community service activity plan, the outputs that will be produced are: for partners, an increase in understanding of the Placement of the Local Workforce. For the proposer, the output to be achieved is in the form of scientific articles and cannot be separated from the Tri Dharma of Higher Education.